REGIONAL BODY COMPOSITION AND MUSCLE STRENGTH ARE RELATED TO BONE MINERAL CONTENT IN ELDERLY - Da Cruz Siqueira, Leandro Oliveira [UNESP]; Machado, Cesar Fernandes [UNESP]; Siminato, Astor Reis [UNESP]; Sancassani, Andrei [UNESP]; Almeida dos Santos, Luiz Gustavo [UNESP]; Takehana Gomes, Larissa Aparecida [UNESP]; Zago, Anderson Saranz [UNESP]; Pessoa Filho, Dalton Muller [UNESP] (Soc Brasileira Med Esporte, 2018)
Introduction: The increase, or maintenance, of lean body mass and muscle strength are major determinants of functional independence in the elderly, since they are associated with bone remodeling, and therefore with a reduced risk of falls and fractures. However, the regional relationship between lean body mass/strength and bone mineral content (BMC) has not sufficient theoretical support. Objective:To analyze whether regional body composition and muscle strength are factors potentially related to BMC. Methods:Ten older men (63.3 +/- 6.4 years, 169.4 +/- 6.8 cm and 79.3 +/- 10.5 kg) underwent body composition assessments using dual energy X-ray absorptiometry (DXA) to obtain regional and whole-body lean mass and BMC measures. The subjects also underwent the one-repetition maximum (1 RM) test involving flat bench press, 45 degrees leg press, arm curl and knee extension. Regional/whole-body composition and 1 RM values were correlated to BMC using Pearson's coefficient (r). The level of significance for the correlations was p 0.05, the confidence interval was 95% (Z(1)-a(/2) =1.96), and the sample power was 80% (1-b). Results: The flat bench press 1 RM was related to BMC in the left (r=0.764) and right (r=0.748) arms, while the 45 degrees leg press 1 RM was associated with BMC in the left (r=0.677) and right (r=0.714) legs and trunk (r=0.810), with sample power of 77.7%, 66.8%, 12.7%, 40.4% and 97.0%, respectively. Whole-body BMC was related to abdominal skinfold (r=0.819), lean mass of left arm (r=0.834), left (r=0.845) and right (r=0.868) legs, and whole-body lean mass (r=0.787), with sample power of 98.4%, 99.6%, 99.9%, 100.0% and 90.1%, respectively. Conclusion: The results supported regional lean body mass as a parameter related to BMC, with potential similar to that consistently reported for whole-body lean mass. Results also suggested that muscle strength plays an important role in improving or maintaining regional and whole-body BMC.
Keywords: Muscle strength; Body composition; Bone density; Aged